"I didn't know you could just ask:" Empowering underrepresented college-bound students to recruit academic and career mentors. (May 2016) - Schwartz, Sarah E.O.; Kanchewa, Stella S.; Rhodes, Jean E.; Cutler, Evan; Cunningham, Jessica L.
Abstract: This study investigates a new approach to cultivating mentoring relationships in which adolescents participate in workshops to develop their capacity to recruit mentors and other supportive adults who can help advance their academic and career goals. Drawing on in-depth pre- and post- interviews, research observations, and participant feedback and workshop materials from a pilot intervention conducted with 12 ethnic minority students in their senior year of high school, this study explores whether and how the intervention influenced participants, as well as mechanisms of change. Results suggested that the intervention increased the value students placed on social capital and mentoring relationships, developed their knowledge, skills, and self-efficacy in how to develop such connections, and influenced their interactions with potential academic and career mentors. Although additional research is needed, this study highlights the potential of a relatively low-cost intervention to support underrepresented college-bound students in developing relationships that are crucial to college and career success. Highlights: A new approach to mentoring that teaches youth to connect with supportive adults is proposed. Participation can increase youth's self-efficacy in reaching out to potential mentors. The intervention shows particular promise for underrepresented college-bound students.